Antimicrobial Properties of Endophytic Fungal Culture Filtrates from Tinospora crispa - Oktira Roka Aji; Karomah Indah Fitria; Naresh Wari Mega Vianingtyas; Adelyanty Pangestuty Wicaksono (Biology, Medicine, & Natural Product Chemistry, 2025)
Endophytic fungi can produce bioactive compounds that are useful as antimicrobials. This study evaluates the antimicrobial potential of culture filtrate extracts derived from endophytic fungi isolated from the medicinal plant Tinospora crispa. Isolation was carried out from the roots, leaves, and stems of T. crispa, which were then identified based on the ITS gene. The culture filtrate was extracted using ethyl acetate and assessed for antimicrobial activity using the disc diffusion method against Escherichia coli, Staphylococcus aureus, and Candida albicans. A total of 3 endophytic fungal isolates were isolated and identified as Acrocalymma vagum, Diaporthe tulliensis, and Colletotrichum truncatum. The results showed that all culture filtrate extracts of the fungal endophyte isolates exhibited varying antimicrobial activity, with the highest antibacterial activity demonstrated by C. truncatum isolates against Escherichia coli and Staphylococcus aureus. The most significant anticandida activity was by D. tulliensis isolates. Endophytic fungi of medicinal plant T. crispa can be developed as a source of antimicrobial agents, especially to overcome the increasing antibiotics resistance.